2006
DOI: 10.1109/jlt.2006.872315
|View full text |Cite
|
Sign up to set email alerts
|

A novel optical waveguide microcantilever sensor for the detection of nanomechanical forces

Abstract: This study presents a novel generic multipurpose probe based on an array of 20 waveguide channels with microcantilevers acting as optical waveguides operated in the visible range. The principle of operation is based on the sensitivity of energy transfer between two butt-coupled waveguides to their misalignment with respect to each other. The technique can be considered an alternative to the known methods used for the readout of the nanomechanical response of microcantilevers to the external force exerted on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
48
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 17 publications
(22 reference statements)
4
48
0
1
Order By: Relevance
“…5,6 Here, we show the development of an integrated optical readout scheme where the cantilever deflection is read out by monitoring the intensity of light traveling through the system via the cantilever. A similar system has been presented by Zinoviev et al 7 with the cantilever fabricated in SiO 2 and the waveguides structured in Si 3 N 4 . However, Si cantilevers are very stiff which is a disadvantage when performing static deflection measurements and a cantilever material of a lower Young's modulus is desirable.…”
mentioning
confidence: 95%
“…5,6 Here, we show the development of an integrated optical readout scheme where the cantilever deflection is read out by monitoring the intensity of light traveling through the system via the cantilever. A similar system has been presented by Zinoviev et al 7 with the cantilever fabricated in SiO 2 and the waveguides structured in Si 3 N 4 . However, Si cantilevers are very stiff which is a disadvantage when performing static deflection measurements and a cantilever material of a lower Young's modulus is desirable.…”
mentioning
confidence: 95%
“…The device was fabricated using the technology reported elsewhere. 9 The waveguide microcantilever made of silicon dioxide is an extension of the silicon dioxide layer thermally grown on silicon substrate. The developed technology allowed fabrication of stress-free silicon dioxide cantilevers.…”
mentioning
confidence: 99%
“…The light propagates until the end of the cantilever and couples into the output waveguide separated from the cantilever by a short gap of 3 m. The coupling efficiency to the output waveguide is a function of the cantilever deflection. 9 The cantilever beam is 600 nm thick, 200 m long, and 40 m wide; the cantilever fundamental resonance mode can be excited at frequency of about 13 kHz. 9 The cantilever waveguide supports two propagating modes for the light wavelength of 633 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 Recently, it was shown that motion of micron-scale devices can be monitored through changes in end-to-end alignment of optical waveguides. [9][10][11] In this letter, we propose an integrated and near-field optical motion detection technique that exploits near-field optical evanescent-wave coupling. We demonstrate that the technique works efficiently for nanoscale mechanical resonators, with greater sensitivity than conventional optical techniques.…”
mentioning
confidence: 99%